Evaluation of Detector Position and Light Fluence Distribution Using an Infrared Navigation System during Pleural Photodynamic Therapy. (16th September 2022) - Sun, Hongjing; Kim, Michele M.; Ong, Yi Hong; Dimoft, Andreea; Singhal, Sunil; Busch, Theresa M.; Cengel, Keith A.; Zhu, Timothy C.
Abstract: Photodynamic therapy (PDT) has been used to treat malignant pleural mesothelioma. Current practice involves delivering light to a prescribed light fluence with a point source, monitored by eight isotropic detectors inside the pleural cavity. An infrared (IR) navigation system was used to track the location of the point source throughout the treatment. The recorded data were used to reconstruct the pleural cavity and calculate the light fluence to the whole cavity. An automatic algorithm was developed recently to calculate the detector positions based on recorded data within an hour. This algorithm was applied to patient case studies and the calculated results were compared to the measured positions, with an average difference of 2.5 cm. Calculated light fluence at calculated positions were compared to measured values. The differences between the calculated and measured light fluence were within 14% for all cases, with a fixed scattering constant and a dual correction method. Fluence‐surface histogram (FSH) was calculated for photofrin‐mediated PDT to be able to cover 80% of pleural surface area to 50 J cm −2 (83.3% of 60 J cm −2 ). The study demonstrates that it will be possible to eliminate the manual measurement of the detector positions, reducing the patient's time under anesthesia. Abstract : Accurate light fluence delivery is crucial to the efficiency of photodynamic therapy (PDT). With an infrared (IR) navigation system, the location of the light point source was tracked throughout PDT. Together with an automatic detector position calculation algorithm, the recorded data was used to calculate the light fluence to the whole cavity after treatment. Fluence‐surface histogram (FSH) was calculated for 8 cases, which demonstrates that, for each case, 80% of pleural surface area is covered to 50 J cm −2 (83.3% of the prescribed does, 60 J cm −2 ).